2006
DOI: 10.2298/spat0614041j
|View full text |Cite
|
Sign up to set email alerts
|

Attic extension and thermal renovation of the residential building: Case study

Abstract: Buildings are the only resource growing constantly. Although relevant data for Serbia is not available, it is presumed that even more than 50% of energy production is spent on buildings in our country. This conclusion is based on two facts: the present industrial production and the state of buildings. In order to establish measures for energy efficient refurbishment, one residential building was analyzed in Belgrade. The chosen building represents the construction period when application of thermal insulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…As shown in case 3, renovation plus vertical extension in a popular location can be financially viable if the apartments are sold off. Jovanović-Popović et al (2006) came to the same conclusion in their study of attic extensions, were they claimed that a preliminary cost analysis showed that selling the apartments in the attic extension paid for the refurbishment of the existing building. Even so, it should be noted that no such cost analysis was presented or referred to in their paper.…”
Section: Strategies For Implementationmentioning
confidence: 75%
See 2 more Smart Citations
“…As shown in case 3, renovation plus vertical extension in a popular location can be financially viable if the apartments are sold off. Jovanović-Popović et al (2006) came to the same conclusion in their study of attic extensions, were they claimed that a preliminary cost analysis showed that selling the apartments in the attic extension paid for the refurbishment of the existing building. Even so, it should be noted that no such cost analysis was presented or referred to in their paper.…”
Section: Strategies For Implementationmentioning
confidence: 75%
“…Because some extension projects might not meet the housing developer’s required rates of return, alternative ways to finance extensions might well be needed. As mentioned earlier, Jovanović-Popović et al (2006) argued that an extension could be financed by selling the apartments in the extension. This argument is also supported by Lidgren and Widerberg (2010), who argued that increasing rent is not always sufficient; instead, selling some apartments could help finance the project.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation